Policy Evaluation of the Governance of Private Higher Education Institutions Under LLDIKTI Region XVI - Abdussamad, Juriko; Gaffar; Tui, Fenti Prihatini Dance (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Coordination and supervision of private universities under LLDIKTI Region XVI still face various challenges in achieving effective governance. This study aims to evaluate and optimize the effectiveness of private university governance under LLDIKTI Region XVI. The research method used is qualitative. Data collection techniques are carried out through observation, interviews, and documentation. The subjects of the study were private university managers in a province. Data analysis was carried out using an inductive approach based on research data. The study results indicate that the effectiveness of private university governance has not reached an optimal level. Four leading indicators contribute to this organization's ineffectiveness: engagement, adaptation, mission, and consistency. Improvements in these four aspects can significantly improve organizational effectiveness. Among the four, engagement significantly influences organizational effectiveness, followed by consistency and adaptation. This study identified three sub-indicators in the consistency aspect. The first sub-indicator is Core values, which include the vision, mission, goals, objectives, and strategies of university governance. The second sub-indicator is agreement, which reflects the unity of the academic community's views on various aspects of university governance. The third sub-indicator is coordination and integration, which measures the extent to which governance runs effectively within the university to drive all organizational units to achieve the established vision. It is concluded that the effectiveness of the governance of provincial private universities under LLDIKTI Region XVI is not yet optimal.